A rare vascular manifestation in chronic myeloid leukemia: a case report and literature review of Bier's spot development during nilotinib treatment - Ahmed Alsaati; Turki Hakami; Sultan Bajawi; Gamil Mohammed; Nouf Bajawi; Nadya Al-Faraidy (Dermatology Reports)
Bier's spots are rare angiospastic macules often associated with physiologic vasoconstriction. This case report describes a 35-year-old man with chronic myeloid leukemia treated with nilotinib who developed Bier's spots, a previously unreported adverse effect of the drug. The patient presented with asymptomatic hypopigmented macules on the hands and legs that appeared during venous stasis and resolved with elevation. This case emphasizes the need to recognize potential vascular side effects of tyrosine kinase inhibitors and highlights Bier's spots as a benign but remarkable manifestation in patients undergoing nilotinib therapy.